Controlling Interfacial Properties of Lithium‐Ion Battery Cathodes with Alkylphosphonate Self‐Assembled Monolayers. Issue 10 (7th March 2018) - Nicolau, Bruno G.; Petronico, Aaron; Letchworth‐Weaver, Kendra; Ghadar, Yasaman; Haasch, Richard T.; Soares, Julio A. N. T.; Rooney, Ryan T.; Chan, Maria K. Y.; Gewirth, Andrew A.; Nuzzo, Ralph G.
Abstract: In this work, the preparation and characterization of modified LiMn2 O4 (LMO) cathodes utilizing chemisorbed alkylphosphonic acids to chemically modify their surfaces are reported. Electrochemical methods to study ionic and molecular mobility through the alkylphosphonate self‐assembled monolayers (SAMs) for different alkyl chain compositions, in order to better understand their impact on the lithium‐ion electrochemistry, are utilized. Electrochemical trends for different chains correlate to trends observed in contact angle measurements and solvation energies obtained from computational methods, indicating that attributes of the microscopic wettability of these interfaces with the battery electrolyte have an important impact on ionic mobility. The effects of surface modification on Mn dissolution are also reported. The alkylphosphonate layer provides an important mode of chemical stabilization to the LMO, suppressing Mn dissolution by 90% during extended immersion in electrolytes. A more modest reduction in dissolution is found upon galvanostatic cycling, in comparison to pristine LMO cathodes. Taken together, the data suggest that alkylphosphonates provide a versatile means for the surface modification of lithium‐ion battery cathode materials allowing the design of specific interfaces through modification of organic chain functionalities. Abstract : Lithium‐ion battery cathode surfaces are decorated with alkylphosphonate self‐assembled monolayers (SAMs). Electrochemical characterization shows that alkylphosphonate layer choice impacts electrochemical behavior, a consequence of the affinity of the SAM with the battery electrolyte. Computational studies report on SAM‐electrolyte and SAM‐cathode stability. Lithium‐ion half cells constructed with SAM modified cathodes show that surface modification leads to reduction in capacity fade.